Growth mechanism and photocatalytic properties of SrWO4 microcrystals synthesized by injection of ions into a hot aqueous solution - Cavalcante, L. S. [UNESP]; Sczancoski, J. C. [UNESP]; Batista, N. C.; Longo, Elson [UNESP]; Varela, José Arana [UNESP]; Orlandi, Marcelo Ornaghi [UNESP] (Elsevier, 2013)
This paper reports our initial research to obtain SrWO4 microcrystals by the injection of ions into a hot aqueous solution and their photocatalytic (PC) properties. These microcrystals were structurally characterized by X-ray diffraction (XRD), Rietveld refinements and Fourier transform (FT)-Raman spectroscopy. The shape and average size of these SrWO 4 microcrystals were observed by field emission scanning electron microscopy (FE-SEM) and transmission electron microscopy (TEM). In addition, we have investigated the PC activity of microcrystals for the degradation of rhodamine B (RhB) and rhodamine 6G (Rh6G) dyes. XRD patterns, Rietveld refinement data and FT-Raman spectroscopy confirmed that SrWO4 microcrystals have a scheelite-type tetragonal structure without deleterious phases. FT-Raman spectra exhibited 12 Raman-active modes in a range from 50 to 1000 cm-1. FE-SEM and TEM images suggested that the SrWO4 microcrystals (rice-like - 95%; star-, flower-, and urchin-like - 5%) were formed by means of primary/secondary nucleation events and self-assembly processes. Based on these FE-SEM/TEM images, a crystal growth mechanism was proposed and discussed in details in this work. Finally, a good PC activity was first discovered of the SrWO4 microcrystals for the degradation of RhB after 80 min and Rh6G after 50 min dyes under ultraviolet-light, respectively. © 2012 The Society of Powder Technology Japan. Published by Elsevier B.V. and The Society of Powder.
Keywords: Hot-injection; Photocatalysis; Rhodamine; Rietveld refinement; SrWO4; Average size; Crystal growth mechanism; Field emission scanning electron microscopy; FT- Raman spectroscopy; FT-Raman spectrum; Growth mechanisms; Photo-catalytic; Photocatalytic property; Raman active modes; Rhodamine 6G; Rhodamine B; Self assembly process; TEM images; Tetragonal structure; Transmission electron microscopy tem; Urchin-like; XRD patterns; Crystal growth; Field emission microscopes; Raman spectroscopy; Solutions; Transmission electron microscopy; Tungstate minerals; X ray diffraction; Microcrystals